Biomechanical Uniaxial Analysis of Porcine Tendon in the CellScale BioTester® 5000 - Fofiu Alexandru; Arbănaşi Emil M.; Tripon Robert G.; Suzuki Shuko; Chirilă Traian V.; Băţagă Tiberiu (Journal of Interdisciplinary Medicine, 2023)
The study was aimed to evaluate whether a mechanical biaxial tester can be used in a uniaxial mode to evaluate the mechanical properties of tendons.